2023
DOI: 10.1039/d3sc00072a
|View full text |Cite
|
Sign up to set email alerts
|

Empowering boronic acids as hydroxyl synthons for aryne induced three-component coupling reactions

Abstract: Boronic acids have become one of the most prevalent classes of reagents in modern organic synthesis, displaying various reactivity profile via C-B bond cleavage. Herein, we describe the utilization of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…17 Despite the enormous difficulties encountered during the COVID-19 pandemic in China, we successfully executed our idea and presented a proof-of-concept application of a boronic acid as the hydroxy source in three-component ring-opening hydroxylation reactions (Scheme 5). 18 Compared to water and metal hydroxides, this in situ formed B-F complex can convey a unique reactivity paradigm, leading to versatile alcohol products in moderate to good yields. Moreover, a systematic investigation on structure-activity relationships suggested that harnessing the electronic and steric parameters around the boron center of the boronic acid could permit the effective modulation of its reactivity toward B-O bond cleavage, thereby rendering it a tunable…”
Section: Cluster Account Synlettmentioning
confidence: 99%
“…17 Despite the enormous difficulties encountered during the COVID-19 pandemic in China, we successfully executed our idea and presented a proof-of-concept application of a boronic acid as the hydroxy source in three-component ring-opening hydroxylation reactions (Scheme 5). 18 Compared to water and metal hydroxides, this in situ formed B-F complex can convey a unique reactivity paradigm, leading to versatile alcohol products in moderate to good yields. Moreover, a systematic investigation on structure-activity relationships suggested that harnessing the electronic and steric parameters around the boron center of the boronic acid could permit the effective modulation of its reactivity toward B-O bond cleavage, thereby rendering it a tunable…”
Section: Cluster Account Synlettmentioning
confidence: 99%
“…11 Arynes are highly reactive electrophiles widely used for producing polysubstituted benzene derivatives. 12 Due to their susceptibility to nucleophilic attack, arynes have been used in several multi-component reactions with CO 2 , and secondary/tertiary aromatic amines in reactions with CO 2 and arynes to generate anthranilic acids and esters. 13 Additionally, Yoshida et al reported the successful incorporation of linear imines with arynes and CO 2 , leading to valuable benzoxazinones through a [2 + 2 + 2] annulation process, although their study only focused on linear imines.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the discovery of Kobayashi precursors, aryne chemistry has witnessed a renaissance in recent years, leading to the development of numerous novel transformations. , These unique methods feature mild conditions, the absence of transition metals, and operational simplicity, thereby allowing the development of molecular complexity with a high efficacy. Given our long-standing interest in the combination of aryne species with organosulfur compounds, we naturally questioned whether the polarizable aryne with a low-lying LUMO could exhibit sufficient “soft” electrophilic character to pair the reactivity with the “soft” sulfur center of sulfenamides to empower chemoselective S -arylation . Although the tentative pathway was proposed on the basis of insights gained from our previous research, we still anticipated several associated challenges .…”
mentioning
confidence: 99%
“…The control experiment using heavy water suggested no incorporation of deuterium into the substrate in the presence of TBAF in THF, which might provide evidence to support the direct S -arylation pathway. On the basis of this finding and the literature, a tentative mechanism was proposed, as shown in Scheme . First, the nucleophilic addition of sulfenamide to aryne formed in situ led to key sulfonium zwitterion intermediates A .…”
mentioning
confidence: 99%